How use the motion capture system in training - Shestakov, M.; Kashcheev, A.; Tokunov, E.; Martynov, P. (6th Conference - Coordination abilities in physical education, sports and rehabilitation, 2015)
Introduction. A technology of 3D analysis based on high-speed video recording is widely accepted and used in different spheres of human activity. A 3D model gives an accurate and detailed image of any object or physical motion. A Qualisys (Sweden) Motion Capture System was part of a testing complex used by the Russian national teams during their preparation for the Winter Olympic games 2014. Test results helped coaches and researchers assess physical condition and preparedness of athletes for competitive performance, estimate exercise technique under field conditions, obtain input data for simulation modeling of exercise technique with the help of specific software packages. Methods. The test complex consisted of 18 cameras Oqus 300 (AB Qualisys, Sweden), two AMTI force plates (AMTI, USA), and Cortex gas analyzer (Cortex, Germany). Recording was done at frame rate 200 fps and synchronized with force plate`s signals. 54 passive light-reflecting markers were fixed on an athlete`s body to identify the skeletal model of his body. Top Russian athletes, candidates for National Olympic teams in cross-country skiing (n=18), bobsleighing (n=24), ski jumping (n=8), Nordic combined (n=8), freestyle skiing moguls (n=18), curling (n=6), luge (6), biathlon (12), speed scating (4), curling (6). As a rule, testing was done at the end of each stage of a year-long training cycle. Testing procedures were adjusted taking into account specificity of every sport discipline. The adjustment concerned the scheme of light-reflecting markers on the athlete`s body, selection and sequence of movement patterns to be performed. Specific software packages for data processing and generating of final protocols for coaches were developed. Results. Cyclic sports (cross-country skiing, Nordic combined, biathlon). Curvilinear (quadratic) relationship between energy expenditure and velocity of cyclic locomotion permits to calculate an optimal speed of movement that requires minimal energy expenditure. Functional capacity and effectiveness of energy supply in skiers and biathletes was estimated during a graded exercise test performed on an extra-wide treadmill (Fitnex, USA) that permitted the use of roll skis. Gasometry and pulse measurement made it possible to calculate aerobic and anaerobic thresholds, maximal oxygen consumption, aerobic capacity, stroke volume, pulse cost of the exercise (number of heart beats per a unit of distance), and anaerobic capacity, i.e. a set of parameters which reflected metabolic efficacy of the exercise. High-speed video records helped to estimate mechanical efficacy of the locomotion at each stage of the test taking into account intra-cyclic angular and temporal parameters of displacement of lower extremities` joints and the center of mass, as well as changes in potential and kinetic energy of the athlete`s body. Sports based on strength&velocity qualities. After a warm-up, the athletes performed vertical jumps: 1) from a half-squat position (the angle in the knee joint 90°) with the arms swing and then whithout the arms swing, 2) after jumping down from the height 10 cm, 30 cm, and 50 cm with the arms swing and then without the arms swing. Each athlete performed three attempts of every type of a jump trying to jump as high as possible. The following parameters were registered in each trial: vertical displacement of the body center of mass, total power, angular velocity, amplitude, force moments in hip, knee and ankle joints in the shock absorption phase and in the take-off phase. The simulation software AnyBody Modeling System (AnyBody Technology A/S, Denmark) was applied in order to calculate the maximal possible height of every jump performed by each subject. Calculation was based on potential force of contraction that could be manifested by every muscle in the subject`s body. Simulation results help coaches to estimate potential abilities of the athletes and develop individual plans of strength training for each of them. Besides vertical jumps from a half-squat position described above, the athletes performed tests specific for their sport discipline. Specific tests revealed crucial aspects of movement patterns in competitive exercises. Bobsleighing. The athletes were asked to push a trolley (weight 100 kg) simulating sleigh acceleration at the starting area. Recording of the three starting steps permitted to determine velocity, absolute value and direction of the force applied to the trolley. Ski jumping and Nordic combined. Ski jumpers and Nordic combined athletes simulated a take-off from the ramp. The same parameters as in vertical jumps were registered: vertical displacement of the body center of mass, total power, angular velocity, amplitude, force moments in hip, knee and ankle joints in the shock absorption phase and in the take-off phase. Freestyle skiing. Freestyle skiers performed 30 jumps from side to side over a rope fixed at the height of 30 cm. The task was to make jumps as fast as possible. Each athlete performed two jumping series. Speed skating and short track speed skating. Skating the straight parts and the curves was recorded under field conditions during ice training sessions. Curling. Each curling player performed 30 deliveries (3 deliveries to each of 5 targets with right and left turns). The task was to place the stone as close to the target as possible. Aerodynamics study. Methods of aerodynamic calculations in sport researches are based on estimation of aerodynamic forces, which affect a moving object (or a system of objects) with unstable configuration. Aerodynamic effects on athletes were examined in ski jumping (jumping hill K-135 in Krasnaya Polyana), speed skating, bobsleigh, and luge. At the first stage of aerodynamic study athletes performed competitive exercises under field conditions. Then the data were processed by the FlowVision software simulating aerodynamic behavior in order to estimate the effect of aerodynamic forces on the athlete`s body throughout the exercise. Initial data processing was performed using the software QualisysTrackManager and TC2 3D-BodyScannerNX-16. Software packages AutodeskMaya, Autodesk 3DStudioMAX, AutodeskMotionBuilder, and AutodeskMudbox were applied for final data processing. Visualization of the approach air flow structure helped to estimate deviation of the flow vector from the initial approach air flow vector. These deviations are referred to as swirl areas. Any swirl area on the body surface results from local deviation of the air flow caused by changes in the local curvature of the athlete`s body or equipment. All aerodynamic disturbances change air resistance to the athlete`s motion. According to the laws of aerodynamics, distribution of pressure and air flow velocity around the athlete`s body and equipment permitted to calculate characteristics of the air flow and estimate their effect on the aerodynamic drag.